Potential Analysis of Islamic Bank Human Resources in East Kalimantan - Yanti, Dharma; Noni, Yovanda; Parlina, Tika (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study aims to see the potential for developing human resources of Islamic banks in East Kalimantan Province. This research is a qualitative and descriptive research, where the data is obtained through library research. Based on the literature study method that has been carried out, several potential human resource development in East Kalimantan have been found, including a large Muslim population (especially in Samarinda City, Kutai Kartanegara Regency, and Balikpapan City, high value of the East Kalimantan Province human development index, support for education. Sector which is reflected through the availability of Islamic Banking/Sharia Economics study programs / Sharia Economic Law at Universities / Institutes / Universities in East Kalimantan, Stability of Sharia Banking Asset Development in East Kalimantan Province. This makes East Kalimantan one of the areas that have potential or opportunities to overcome the problem of limited human resources both in terms of quality and quantity. Where the expected human resources are those who understand the principles of Islamic banking comprehensively.